Analysis of UML Activities Using Dynamic Meta Modeling - Engels, Gregor; Soltenborn, Christian; Wehrheim, Heike (Formal Methods for Open Object-Based Distributed Systems, 9th IFIP WG 6.1 International Conference, FMOODS 2007, Paphos, Cyprus, June 6-8, 2007, Proceedings)

Refactoring Object-Oriented Specifications with Data and Processes - Ruhroth, Thomas; Wehrheim, Heike (Formal Methods for Open Object-Based Distributed Systems, 9th IFIP WG 6.1 International Conference, FMOODS 2007, Paphos, Cyprus, June 6-8, 2007, Proceedings)

The Challenges of Building Advanced Mechatronic Systems - Schäfer, Wilhelm; Wehrheim, Heike (International Conference on Software Engineering, ISCE 2007, Workshop on the Future of Software Engineering, FOSE 2007, May 23-25, 2007, Minneapolis, MN, USA)

Proving Linearizability Via Non-atomic Refinement - Derrick, John; Schellhorn, Gerhard; Wehrheim, Heike (Integrated Formal Methods, 6th International Conference, IFM 2007, Oxford, UK, July 2-5, 2007, Proceedings)

Global Shift – The European Union, the United States, and the Emergence of China - Gries, Thomas (50 Years of EU Economic Dynamics)

Educational Disparity and Income Inequality in Urban China - Gries, Thomas; Xue, Jinjun (The Economic Science)

Local Polynomial Estimation with a FARIMA-GARCH Error Process - Beran, Jan; Feng, Yuanhua (Bernoulli)

Identification of services --- A stakeholder-based approach to SOA development and its application in the area of production planning - Klose, Karsten; Knackstedt, Ralf; Beverungen, Daniel (Proceedings of the 15th European Conference on Information System)

Bereitstellung von Artikelstammdaten - Becker, Jörg; Winkelmann, Axel; Beverungen, Daniel; Janiesch, Christian (HMD --- Praxis der Wirtschaftsinformatik)

Measurement of learning culture: a motivational approach - Bauer, J; Rehrl, M; Harteis, Christian (Learning in the workplace--new developments)

Über die Rolle epistemischer Überzeugungen für die Gestaltung von E-Learning—eine empirische Studie bei Hochschullehrendenn - Gruber, Hans; Harteis, Christian; Hasanbegovic, Jasmina; Lehner, Franz (Neue Trends im E-Learning)

Epistemological beliefs and their impact on the practice of e-learning in companies - Harteis, Christian; Gruber, Hans; Hertramph, Herbert (Computers and advances technologies in education. Globalization of education through advanced technology)

Learning from errors in the workplace--insights from two studies in Germany and Finland - Harteis, Christian; Bauer, Johannes; Haltia, Petri (Learning in the workplace--new developments)

Die steuerliche Ungleichbehandlung von Anteilen an Kapitalgesellschaften - Müller, Jens (Finanz Betrieb)
Das Bundesverfassungsgericht hat die aktuelle Erbschaft- und Schenkungsteuer für verfassungswidrig erklärt. Verantwortlich hierfür sind insbesondere die unterschiedlichen Bewertungen der einzelnen Vermögenspositionen. In diesem Beitrag wird die steuerliche Unter- oder Überbewertung von Anteilen an Kapitalgesellschaften untersucht. Durch Sensitivitätsanalysen wird illustriert, in welchem Maß ökonomische Rahmenbedingungen die Wertlücke zwischen Steuer- und Marktwert verändern. Die Ergebnisse zeigen, dass die geltenden steuerlichen Bewertungsvorschriften in verschiedenen realistischen Szenarien selbst bei ähnlichen Unternehmenstypen zu einer Ungleichbehandlung führen.
Keywords: Anteile Kapitalgesellschaften; Rahmenbedingung; Wertlücke; steuerliche Ungleichbehandlung

Participation as predictor of responsibility in working life - Festner, Dagmar; Harteis, Christian; Kyhä, Henna; Tuominen, T (Learning in the workplace - new developments in the relation between learning and working)

Tamper Resistance of AES -- Models, Attacks and Countermeasures - Krummel, Volker

Analysis of Countermeasures Against Access Driven Cache Attacks on AES - Blömer, Johannes; Krummel, Volker (Selected Areas in Cryptography)

Cryptanalysis of Unbalanced RSA with Small CRT-Exponent - May, Alexander (Advances in Cryptology — CRYPTO 2002)

Low Secret Exponent RSA Revisited - Blömer, Johannes; May, Alexander (Lecture Notes in Computer Science)

Key Revocation with Interval Cover Families - Blömer, Johannes; May, Alexander (Selected Areas in Cryptography)

Dimension Reduction Methods for Convolution Modular Lattices - May, Alexander; Silverman, Joseph H. (Lecture Notes in Computer Science)

A Probabilistic Zero-Test for Expressions Involving Roots of Rational Numbers - Blömer, Johannes (Algorithms — ESA’ 98)

Employment Effects of International Factor Mobility - A Theoretical Approach with Heterogenous Labor - Gries, Thomas; Jungblut, Stefan (Journal of Economic Integration)

Pattern of beverage consumption and long-term association with body-weight status in German adolescents – results from the DONALD study - Libuda, Lars; Alexy, Ute; Sichert-Hellert, Wolfgang; Stehle, Peter; Karaolis-Danckert, Nadina; Buyken, Anette; Kersting, Mathilde (British Journal of Nutrition)
In the present study the relationship between the consumption of different beverage groups and body-weight status in 5 years of study participation in German adolescents was investigated. We used anthropometric and dietary data from 3 d weighed records of 244 subjects between 9 and 18 years of age participating in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study. Only subjects with at least four out of six possible weighed dietary records were considered. A repeated-measures regression model (PROC MIXED) was used to analyse the effect of beverage consumption on body-weight status. BMI standard deviation scores (BMI-SDS) and body fat percentage (%BF) were chosen as the dependent variables. In boys, energetic beverage consumption was not associated with BMI-SDS or %BF, neither cross-sectionally nor prospectively. In girls, baseline consumption of energetic beverages did not predict baseline BMI-SDS, baseline %BF, or change in either variable over the study period. However, an increase in energetic beverage consumption over the study period was associated with an increase in BMI-SDS (+0.070 SDS/MJ increase in energetic beverage consumption; P = 0·01). Separate consideration of regular soft drinks and fruit juices revealed that, in girls, BMI-SDS increased with increased fruit juice consumption (+0·096 SDS/MJ increase in fruit juice consumption; P = 0·01), and to a lesser extent with regular soft drink consumption (+0·055 SDS/MJ increase in regular soft drink consumption; P = 0·08). In conclusion, these results suggest that an increase in energetic beverage consumption may result in weight gain, at least in adolescent girls.

DONALD News: Zuckerhaltige Getränke und Übergewicht bei Kindern. - Libuda, Lars; Alexey, U. (Monatsschriften Kinderheilkunde)

Dietary Glycemic Index, Glycemic Load, Fiber, Simple Sugars, and Insulin Resistance: The Inter99 Study: Response to Lau et al. - Buyken, Anette; Liese, A. D. (Diabetes Care)

Type 2 diabetes mellitus and risk of coronary heart disease: results of the 10-year follow-up of the PROCAM study - Buyken, Anette; von Eckardstein, Arnold; Schulte, Helmut; Cullen, Paul; Assmann, Gerd (European Journal of Cardiovascular Prevention & Rehabilitation)

Zum Umgang mit Vielfalt im haushaltsbezogenen Unterricht - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Vermittlung von Konsum- und Finanzkompetenzen für Kinder und Jugendliche - Möglichkeiten und Grenzen pädagogischen Handelns - Schlegel-Matthies, Kirsten (Der pädagogische Blick. Zeitschrift für Wissenschaft und Praxis in pädagogischen Berufen)

REVIS - Moderne Ernährungs- und Verbraucherbildung - Oepping, A.; Schlegel-Matthies, Kirsten

Grammatik der Menschenbezeichner in biographischen Kontexten - Geierhos, Michaela

Informationsextraktion aus Stellenanzeigen im Internet - Bsiri, Sandra; Geierhos, Michaela (LWA 2007: Lernen - Wissen - Adaption, Halle, September 2007, Workshop Proceedings)
Dieser Beitrag beschäftigt sich mit der Informationsextraktion aus Stellenanzeigen im französischsprachigen Web. Ziel dieser Arbeit ist es, unstrukturierte Dokumente in Repräasentationsvektoren anhand lokaler Grammatiken zu transformieren. Auf diese Weise wird es möglich, den Stellenmarkt für Jobsuchmaschinen transparenter zu gestalten, indem nur auf dem Inhalt der Anzeige in Form von Darstellungsvektoren anstatt auf unübersichtlichem Fließtext gesucht werden muss.

Program evaluation using fuzzy logic with bad smells as inputs - Delic, A.; Avdagic, Z.; Schäfer, Wilhelm; Boskovic, Dusanka; Meyer, Matthias (Proc. of the 21st International Symposium on Information, Communication and Automation Technologies (ICAT 2007), Sarajevo, Bosnia Herzegovina)

Flexible dezentrale Administration überschneidender Benutzergruppen – Informationelle Selbstbestimmung durch benutzerkontrollierte Provisionierung - Brennecke, Andreas; Finke, Stefan; König, J.; Oevel, Gudrun (Konferenzband der 20. DFN-Jahrestagung DFN2006)

Ernst Zermelo. An Approach to His Life and Work - Ebbinghaus, Heinz-Dieter; Peckhaus, Volker
Rezension: Neue Zürcher Zeitung v. 6. Juni 2007 (G. Szpiro); Ralf Bülow, “Hundert Jahre moderne Mathematik”, heise online v. 13.02.2008 (http://www.heise.de/newsticker/Hundert-Jahre-moderne-Mathematik–/meldung/103411); Mathematical Reviews 2007m:01024 (J.M. Plotkin); MAA Online 5. Juli 2007 (M. Berg); Philip J. Davis, “The Z of ZF and ZFC and ZF¬C”, SIAM News 41.1, January/February 2008; SIAM Review 50.1 (2008), 167–169; (J.W. Dawson); European Mathematical Society Newsletter June 2008, 54; The Mathematical Intelligencer 31 (2009), 79–81 (Henry E. Heatherly); Notices of the AMS 56 (2009), 823–827 (G.H. Moore); Zbl. Math. 1176.01001 (H.K. Sørensen).

Der Mathematikunterricht 53, H. 5: Schwerpunkt: Philosophie und Mathematik

Correlation Effects in Disordered Metallic Photonic Crystal Slabs - Nau, D.; Schönhardt, A.; Bauer, Ch.; Christ, A.; Zentgraf, Thomas; Kuhl, J.; Klein, M. W.; Giessen, H. (Physical Review Letters)

Lorentz model for metamaterials: Optical frequency resonance circuits - Meyrath, T. P.; Zentgraf, Thomas; Giessen, H. (Physical Review B)

Guarding our digital society's well-being - Leonardi, Stefano; Mahlmann, Peter; Meyer auf der Heide, Friedhelm; Spirakis, Paul G.; Weikum, Gerhard (e-Strategies, www.britishpublishers.com)

Ultrabroadband 50-130 THz pulses generated via phase-matched difference frequency mixing in LiIO_3 - Zentgraf, Thomas; Huber, Rupert; Nielsen, Nils C.; Chemla, Daniel S.; Kaindl, Robert A. (Optics Express)

The origin of magnetic polarizability in metamaterials at optical frequencies - an electrodynamic approach - Rockstuhl, Carsten; Zentgraf, Thomas; Pshenay-Severin, Ekaterina; Petschulat, Jörg; Chipouline, Arkadi; Kuhl, Jürgen; Pertsch, Thomas; Giessen, Harald; Lederer, Falk (Optics Express)

Babinet’s principle for optical frequency metamaterials and nanoantennas - Zentgraf, Thomas; Meyrath, T. P.; Seidel, A.; Kaiser, S.; Giessen, H.; Rockstuhl, C.; Lederer, F. (Physical Review B)

Resonance hybridization in double split-ring resonator metamaterials - Guo, Hongcang; Liu, Na; Fu, Liwei; Meyrath, Todd P.; Zentgraf, Thomas; Schweizer, Heinz; Giessen, Harald (Optics Express)

Enhanced transmission of periodic, quasiperiodic, and random nanoaperture arrays - Rockstuhl, Carsten; Lederer, Falk; Zentgraf, Thomas; Giessen, Harald (Applied Physics Letters)

Optical properties of disordered metallic photonic crystal slabs - Nau, D.; Schönhardt, A.; Christ, A.; Zentgraf, Thomas; Bauer, Ch.; Kuhl, J.; Giessen, H. (physica status solidi (a))

Dynamics and dephasing of plasmon polaritons in metallic photonic crystal superlattices: Time- and frequency-resolved nonlinear autocorrelation measurements and simulations - Utikal, Tobias; Zentgraf, Thomas; Kuhl, Jürgen; Giessen, Harald (Physical Review B)

The valency of experiential and evaluative adjectives - Mindt, Ilka (Valency. Theoretical, Descriptive and Cognitive Issues)

Why Robots Need Maps - Dynia, Miroslaw; Łopuszański, Jakub; Schindelhauer, Christian (Proc. of the 14th Colloquium on Structural Information and Communication Complexity (SIROCCO))

Competitive Maintenance of Minimum Spanning Trees in Dynamic Graphs - Dynia, Miroslaw; Korzeniowski, Miroslaw; Kutyłowski, Jarosław (Proc. of the 33rd International Conference on Current Trends in Theory and Practice of Computer Science (SOFSEM'07))

Using Mobile Relays for Ensuring Connectivity in Sparse Networks - Kutylowski, Jaroslaw

Competitive Maintenance of Minimum Spanning Trees under Stochastic Adversaries - Kutylowski, Jaroslaw

Wort/Spiele. Drama – Film – Literatur - Eke, Norbert Otto

Tiere, Texte, Spuren

„Zwischen Utopie und Realität. Die ‚Idealstadt’ Jülich als Ausdruck des frühneuzeitlichen Ordnungsdenkens“ - Seng, Eva- Maria (Jülicher Geschichtsblätter Bd. 73)

Jörg Held (um 1454-1527), Petrarca-Meister, Vogelschau der Stadt Augsburg - Seng, Eva- Maria (Geschichte der bildenden Kunst in Deutschland, Bd. 4 Spätgotik und Renaissance)

Grausame Spiegel. Lenaus Blick zurück nach vorn: Die Albigenser. Freie Dichtungen - Eke, Norbert Otto (Von Sommerträumen und Wintermärchen. Versepen im Vormärz)

Tiere, Texte, Spuren (Vorwort) - Eke, Norbert Otto; Geulen, Eva (Tiere, Texte, Spuren)

Im „deutschen Zauberwald“. Spiegel- und Kippfiguren des Antisemitismus in deutschsprachiger Gegenwartsliteratur - Eke, Norbert Otto (Literarischer Antisemitismus nach Auschwitz)

„Nichts, was einen Anfang hatte, ist unendlich.“ Robert Menasses Arbeit an der Differenz – Die Zerstörung der Welt als Wille und Vorstellung. Frankfurter Poetikvorlesungen - Eke, Norbert Otto (Was einmal wirklich war. Zum Werk Robert Menasses)

Das ‚kleine Sagen’ und das ‚große Sagen’. Herta Müllers Gegenschrift - Eke, Norbert Otto (Walter-Hasenclever-Gesellschaft. Jahrbuch 2005/2006)

Schreckbilder: Die Revolution als Aufstand der ‚schwarzen Männer’ - Eke, Norbert Otto (Das Unterhaltungsstück um 1800. Literaturhistorische Konfigurationen – Signaturen der Moderne. Zur Geschichte des Theaters als Reflexionsmedium von Gesellschaft, Politik und Ästhetik)

A CUDA-Supported Approach to Remote Rendering - Lietsch, Stefan; Marquardt, Oliver (Proc. Int. Symp. on Visual Computing (ISVC))

Comparing Fault Tolerance Mechanisms for Self-Organizing Resource Management in Grids - Voss, Kerstin (Proc. Int. Conf. on Semantics, Knowledge and Grid (SKG))

Gaining Users' Trust by Publishing Failure Probabilities - Battré, Dominic; Djemame, Karim; Kao, Odej; Voss, Kerstin (Proc. Int. Conf. on Security and Privacy in Communications Networks (SecureComm))

Increasing the Reliability of Wireless Sensor Networks with a Unit Testing Framework - Beutel, Jan; Plessl, Christian; Woehrle, Matthias

AssessGrid, Economic Issues Underlying Risk Awareness in Grids - Voss, Kerstin; Djemame, Karim; Gourlay, Iain; Padgett, James (Proc. Int. Worksh. on Grid Economics and Business Models (GECON))

Enhance Self-managing Grids by Risk Management - Voss, Kerstin (Proc. Int. Conf. on Networking and Services (ICNS))

Computational Steering of Interactive and Distributed Virtual Reality Applications - Lietsch, Stefan; Zabel, Henning; Berssenbruegge, Jan (Proc. ASME Computers and Information in Engineering Conference (CIE))

Gather and Prepare Monitoring Data for Estimating Resource Stability - Birkenheuer, Georg; Majlender, Peter; Nitsche, Holger; Voss, Kerstin; Weber, Elmar (Proc. Cracow Grid Workshop (CGW))

Verteilte Berechnung und Darstellung automobiler Scheinwerfer - Berssenbrügge, Jan; Lietsch, Stefan (Proc. Worksh. Augmented & Virtual Reality in der Produktentstehung)

Orientation in a Trail Network by Exploiting its Geometry for Swarm Robotics - Dorigo, Marco; Hamann, Heiko; Szymanski, Marc; Wörn, Heinz; Shi, Yuhui (IEEE Swarm Intelligence Symposium, Honolulu, USA, April 1-5)

The effect of phosphatidylserine on golf performance. - Jäger, R; Purpura, M; Geiss, KR; Weiß, M; Baumeister, Jochen; Amatulli, F; Schröder, L; Herwegen, H (J Int Soc Sports Nutr)

An analytical and spatial model of foraging in a swarm of robots - Hamann, Heiko; Wörn, Heinz; Sahin, Erol; Spears, Winfield; Winfield, Winfield (Swarm Robotics - Second SAB 2006 International Workshop)

A Space- and Time-Continuous Model of Self-Organizing Robot Swarms for Design Support - Hamann, Heiko; Wörn, Heinz (First International Conference on Self-Adaptive and Self-Organizing Systems (SASO 2007))
Designing and implementing artificial self-organizing systems is a challenging task since they typically behave non- intuitive and only little theoretical foundations exist. Predicting a system of many components with a huge amount of interactions is beyond human skills. The currently common use of simulations for design support is not satisfying, as it is time-consuming and the results are most likely sub- optimal. In this work, we present the derivation of an analytical, time-, and space-continuous model for a swarm of autonomous robots based on the Fokker-Planck equation. While the motion model is in most parts physically motivated, the communication model is based on a heuristic approach. A showcase application to a recently proposed scenario of collective perception in a huge swarm of robots with very limited abilities is given and the simulation results are compared to the model. Despite the high level of abstraction, the prediction discrepancies are small and the parameters can be mapped one-to-one from the model to the control algorithm. Finally, we give an outlook on the capabilities of the proposed model, discuss its limitations, and suggest an improvement that could reduce the number of empirically determined parameters.

Embodied Computation - Hamann, Heiko; Wörn, Heinz; Nagy, Marius; Nagy, Naya (Parallel Processing Letters)

From Micro to Nano and Swarm Robotics - Hamann, Heiko; Szymanski, Marc; Wörn, Heinz; Estana, Ramon; Xie, Ming; Dubowsky, Steven (Advances in Climbing and walking robots. Proceedings of 10th International Conference (CLAWAR'07), Singapore, July 16-18)
Current research in Micro, Nano and Swarm Robots as results of the European projects Miniman, MiCRoN and I-SWARM will be presented. First, the design and the control of 5 to 10cm3 sized mobile micro robots with five degrees of freedom will be shown. They can handle miniaturized parts as for example an optical component or a biological cell with a size in the micrometre-area with an accuracy of 100nm under a microscope or a raster-electron microscope. Second, the design and the control of a 1cm3-sized mobile untethered micro robot will be demonstrated. Here, the robot consists of five parts: the Piezzo locomotion module, the micro control unit, the communication unit, the navigation system and the micro gripper. The mobile robot can be guided and positioned in an arena with an accuracy of 5 micrometre and can be programmed and controlled over the wireless communication unit. Third, the design and the control of 3 × 3 × 3 mm3 sized micro-/nanorobots with 2 degrees of freedom will be presented. The transmission of energy and the communication between the robots is realized via infrared. The robot controller is fully integrated and has limited functionalities. Via basic sensors communication functions and elementary rules and behaviours the micro robot can act in a swarm consisting of hundreds and thousands of robots. Future applications could be monitoring-, inspection-, exploring-tasks etc. of big areas or objects.

Revising Type-2 Computation and Degrees of Discontinuity - Ziegler, Martin (Electronic Notes in Theoretical Computer Science)

Real Hypercomputation and Continuity - Ziegler, Martin (Theory of Computing Systems)

(Short) Survey of Real Hypercomputation - Ziegler, Martin (Lecture Notes in Computer Science)

Real Computational Universality: The Word Problem for a Class of Groups with Infinite Presentation - Meer, Klaus; Ziegler, Martin (Mathematical Foundations of Computer Science 2007)

On Faster Integer Calculations using Non-Arithmetic Primitives - Lürwer-Brüggemeier, Katharina; Ziegler, Martin (arXiv:0709.0624)
The unit cost model is both convenient and largely realistic for describing integer decision algorithms over (+,*). Additional operations like division with remainder or bitwise conjunction, although equally supported by computing hardware, may lead to a considerable drop in complexity. We show a variety of concrete problems to benefit from such NON-arithmetic primitives by presenting and analyzing corresponding fast algorithms.

Real Computability and Hypercomputation - Ziegler, Martin

Interactive Refinement of a Material Flow Simulation Model by Comparing Multiple Simulation Runs in one 3D Environment - Fischer, Matthias; Laroque, Christoph; Huber, Daniel; Krokowski, Jens; Mueck, Bengt; Kortenjan, Michael; Aufenanger, Mark; Dangelmaier, Wilhelm (European Simulation and Modelling Conference (ESM 2007))
The validation of material flow models as well as the selection of promising strategies for the generation of a successful experiment plan is a time-consuming process. A new approach is presented, which supports the simulation expert in his working process by giving him the opportunity to modify the simulated simulation run and afterwards compare the effects of his modification with the original setting, online and in one user interface, implemented by switching the visualizations between the simulation runs or opening up to 5 parallel 3D windows. The method developed therefore clones existing simulation runs online and allows the navigation within these existing simulation runs. The method has been implemented and is validated by a test model, which describes in detail the new working process of a modeler. New research questions are derived from this work, which will define following working steps.

Ein ganzheitlicher Ansatz zur immersiven 3D-Materialflusssimulation innerhalb der Digitalen Fabrik - Dangelmaier, Wilhelm; Laroque, Christoph; Fischer, Matthias (Augmented & Virtual Reality in der Produktentstehung)

Multiple-Access Relay Channel with Network Coding and Non-Ideal Source-Relay Channels - Woldegebreal, Dereje H.; Karl, Holger (2007 4th International Symposium on Wireless Communication Systems)

Optimizing sleeping intervals in preamble sampling MAC for WSNs - Karl, Holger

Estimating Clustering Indexes in Data Streams - Buriol, Luciana S.; Frahling, Gereon; Leonardi, Stefano; Sohler, Christian (Proceedings of the 15th European Symposium on Algorithms (ESA))
We present random sampling algorithms that with probability at least 1 − δ compute a (1 ±ε)-approximation of the clustering coefficient and of the number of bipartite clique subgraphs of a graph given as an incidence stream of edges. The space used by our algorithm to estimate the clustering coefficient is inversely related to the clustering coefficient of the network itself. The space used by our algorithm to compute the number K 3,3 of bipartite cliques is proportional to the ratio between the number of K 1,3 and K 3,3 in the graph. Since the space complexity depends only on the structure of the input graph and not on the number of nodes, our algorithms scale very well with increasing graph size. Therefore they provide a basic tool to analyze the structure of dense clusters in large graphs and have many applications in the discovery of web communities, the analysis of the structure of large social networks and the probing of frequent patterns in large graphs. We implemented both algorithms and evaluated their performance on networks from different application domains and of different size; The largest instance is a webgraph consisting of more than 135 million nodes and 1 billion edges. Both algorithms compute accurate results in reasonable time on the tested instances.

Interaction of radiation with matter. Part II: Light and electrons - Schindlmayr, Arno (Probing the Nanoworld)

Time-dependent density-functional theory for extended systems - Botti, Silvana; Schindlmayr, Arno; Del Sole, Rodolfo; Reining, Lucia (Reports on Progress in Physics)
For the calculation of neutral excitations, time-dependent density functional theory (TDDFT) is an exact reformulation of the many-body time-dependent Schrödinger equation, based on knowledge of the density instead of the many-body wavefunction. The density can be determined in an efficient scheme by solving one-particle non-interacting Schrödinger equations—the Kohn–Sham equations. The complication of the problem is hidden in the—unknown—time-dependent exchange and correlation potential that appears in the Kohn–Sham equations and for which it is essential to find good approximations. Many approximations have been suggested and tested for finite systems, where even the very simple adiabatic local-density approximation (ALDA) has often proved to be successful. In the case of solids, ALDA fails to reproduce optical absorption spectra, which are instead well described by solving the Bethe–Salpeter equation of many-body perturbation theory (MBPT). On the other hand, ALDA can lead to excellent results for loss functions (at vanishing and finite momentum transfer). In view of this and thanks to recent successful developments of improved linear-response kernels derived from MBPT, TDDFT is today considered a promising alternative to MBPT for the calculation of electronic spectra, even for solids. After reviewing the fundamentals of TDDFT within linear response, we discuss different approaches and a variety of applications to extended systems.

Ab initio study of the half-metal to metal transition in strained magnetite - Friák, Martin; Schindlmayr, Arno; Scheffler, Matthias (New Journal of Physics)
Using density-functional theory, we investigate the stability of the half-metallic ground state of magnetite under different strain conditions. The effects of volume relaxation and internal degrees of freedom are fully taken into account. For hydrostatic compression, planar strain in the (001) plane and uniaxial strain along the [001] direction, we derive quantitative limits beyond which magnetite becomes metallic. As a major new result, we identify the bond length between the octahedrally coordinated iron atoms and their neighbouring oxygen atoms as the main characteristic parameter, and we show that the transition occurs if external strain reduces this interatomic distance from 2.06 Å in equilibrium to below a critical value of 1.99 Å. Based on this criterion, we also argue that planar strain due to epitaxial growth does not lead to a metallic state for magnetite films grown on (111)-oriented substrates.

Quasiparticle calculations for point defects at semiconductor surfaces - Schindlmayr, Arno; Scheffler, Matthias (Theory of Defects in Semiconductors)
We present a quantitative parameter-free method for calculating defect states and charge-transition levels of point defects in semiconductors. It combines the strength of density-functional theory for ground-state total energies with quasiparticle corrections to the excitation spectrum obtained from many-body perturbation theory. The latter is implemented within the G0W0 approximation, in which the electronic self-energy is constructed non-self-consistently from the Green’s function of the underlying Kohn–Sham system. The method is general and applicable to arbitrary bulk or surface defects. As an example we consider anion vacancies at the (110) surfaces of III–V semiconductors. Relative to the Kohn–Sham eigenvalues in the local-density approximation, the quasiparticle corrections open the fundamental band gap and raise the position of defect states inside the gap. As a consequence, the charge-transition levels are also pushed to higher energies, leading to close agreement with the available experimental data.

On Testable Properties in Bounded Degree Graphs - Sohler, Christian; Czumaj, Artur (Proceedings of the 17th ACM-SIAM Symposium on Discrete Algorithms (SODA'07))
We study graph properties which are testable for bounded degree graphs in time independent of the input size. Our goal is to distinguish between graphs having a predetermined graph property and graphs that are far from every graph having that property. It is believed that almost all, even very simple graph properties require a large complexity to be tested for arbitrary (bounded degree) graphs. Therefore in this paper we focus our attention on testing graph properties for special classes of graphs. We call a graph family non-expanding if every graph in this family is not a weak expander (its expansion is O(1/log2 n), where n is the graph size). A graph family is hereditary if it is closed under vertex removal. Similarly, a graph property is hereditary if it is closed under vertex removal. Next, we call a graph property Π to be testable for a graph family F if for every graph G ε F, in time independent of the size of G we can distinguish between the case when G satisfies property Π and when it is far from every graph satisfying property Π. In this paper we prove thatIn the bounded degree graph model, any hereditary property is testable if the input graph belongs to a hereditary and non-expanding family of graphs.As an application, our result implies that, for example, any hereditary property (e.g., k-colorability, H-freeness, etc.) is testable in the bounded degree graph model for planar graphs, graphs with bounded genus, interval graphs, etc. No such results have been known before and prior to our work, in the bounded degree graph model very few graph properties have been known to be testable for any graph classes.

StrSort Algorithms for Geometric Problems - Sohler, Christian; Lammersen, Christiane (Proceedings of the 23rd European Workshop on Computational Geometry (EWCG))
In the StrSort model [2], the input is given as a stream, e.g. a sequence of points, and an algorithm can perform (a) streaming and (b) sorting passes to process the stream. A streaming pass reads the input stream from left to right and writes an output stream, which is the input of the next pass. A sorting pass is a black box operation that sorts a stream according to some partial order. In this paper, we develop algorithms for two basic geometric problems in the StrSort model. At first, we propose a divide-and-conquer algorithm that computes the convex hull of a point set in 2D in O(log2 n) passes using O(1) memory. Then we give a StrSort algorithm to compute a (1+ε)-spanner for a point set in Rd for constant d and constant epsilon that uses O(logd-1 n) passes and O(log n) space. This result implies a (1+ε)-approximation of the Euclidean minimum spanning tree in Rd, for constant d and ε.

Testing Expansion in Bounded-Degree Graphs - Sohler, Christian; Czumaj, Artur (Proceedings of the 48th Annual IEEE Symposium on Foundations of Computer Science (FOCS))

Small Space Representations for Metric Min-Sum k-Clustering and their Applications - Sohler, Christian; Czumaj, Artur (Proceedings of the 24th International Symposium on Theoretical Aspects of Computer Science (STACS'07))

Sublinear-time approximation algorithms for clustering via random sampling - Sohler, Christian; Czumaj, Artur (Random Structures & Algorithms)
We present a novel analysis of a random sampling approach for four clustering problems in metric spaces: k-median, k-means, min-sum k-clustering, and balanced k-median. For all these problems, we consider the following simple sampling scheme: select a small sample set of input points uniformly at random and then run some approximation algorithm on this sample set to compute an approximation of the best possible clustering of this set. Our main technical contribution is a significantly strengthened analysis of the approximation guarantee by this scheme for the clustering problems.The main motivation behind our analyses was to design sublinear-time algorithms for clustering problems. Our second contribution is the development of new approximation algorithms for the aforementioned clustering problems. Using our random sampling approach, we obtain for these problems the first time approximation algorithms that have running time independent of the input size, and depending on k and the diameter of the metric space only. © 2006 Wiley Periodicals, Inc. Random Struct. Alg., 2007A preliminary extended abstract of this work appeared in Proceedings of the 31st Annual International Colloquium on Automata, Languages and Programming (ICALP), pp. 396407, 2004.

A PTAS for k-means clustering based on weak coresets - Sohler, Christian; Monemizahdeh, Morteza; Feldman, Dan (Proceedings of the 23rd annual symposium on computational geometry (SoCG'07))

Efficient kinetic data structures for MaxCut - Sohler, Christian; Czumaj, Artur; Frahling, Gereon (Proceedings of the 19th Canadian Conference on Computational Geometry (CCCG))

Dynamic and redundant data placement - Brinkmann, André; Effert, Sascha; Meyer auf der Heide, Friedhelm; Scheideler, Christian (IEEE International Conference on Distributed Computing Systems (ICDCS))
We present a randomized block-level storage virtualization for arbitrary heterogeneous storage systems that can distribute data in a fair and redundant way and can adapt this distribution in an efficient way as storage devices enter or leave the system. More precisely, our virtualization strategies can distribute a set of data blocks among a set of storage devices of arbitrary non-uniform capacities so that a storage device representing x% of the capacity in the system will get x% of the data (as long as this is in principle possible) and the different copies of each data block are stored so that no two copies of a data block are located in the same device. Achieving these two properties is not easy, and no virtualization strategy has been presented so far that has been formally shown to satisfy fairness and redundancy while being time- and space-eflcient and allowing an efficient adaptation to a changing set of devices.

Von der Mechatronik zur Selbstoptimierung - Frank, Ursula; Gausemeier, Jürgen; Schmidt, Alexander; Zimmer, Detmar (Internationales Forum Mechatronik. Intelligente Systeme und Module)